ACCIDENT PATTERNS IN OIL AND GAS PIPELINE DISTRIBUTION SYSTEMS - Mysak, Pavlo; Mysak, Ihor (European Science, 2025)
This paper examines the causes of accidents in oil and gas pipeline systems, highlighting key trends and regional differences. It traces the historical evolution of pipeline infrastructure and the growing role of regulations in enhancing safety and effici